tìm x (x^2 -1) (x^4+x^2+1) (x^2 -1) = 0 (x-2)^3 – (x-3) (x^2+3x +9+6) (x+1)^2=49

Question

tìm x (x^2 -1) (x^4+x^2+1) (x^2 -1) = 0
(x-2)^3 – (x-3) (x^2+3x +9+6) (x+1)^2=49

in progress 0
Kinsley 5 ngày 2021-09-09T14:21:32+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-09-09T14:23:30+00:00

    Đáp án:

     a. `S={0; +-1}`

    b. `S={-2+\sqrt{10}; -2-\sqrt{10}}`

    Giải thích các bước giải:

    a.  \(x(x^2-1)(x^4+x^2+1)(x^2-1)=0\\\to x{(x^2-1)}^2(x^4+x^2+1)=0\\\to \left[ \begin{array}{l}x=0\\x^2-1=0\\ x^4+x^2+1=0\end{array} \right.\\\to \left[ \begin{array}{l}x=0\\x=\pm1\end{array} \right.\) 

    Vậy nghiệm của phương trình là: `S={0;+-1}`

    b. 

    \((x-2)^3 – (x-3) (x^2+3x +9)+6 (x+1)^2=49\\\Leftrightarrow x^3-2x^2+4x-8-(x^3-27)+6(x^2+2x+1)=49\\\Leftrightarrow x^3-2x^2+4x-8-x^3+27+6x^2+12x+6=49\\\Leftrightarrow 4x^2+16x+25=49\\\Leftrightarrow x^2+4x=6\\\Leftrightarrow x^2+4x-6=0\)

    \(\Leftrightarrow x^2+4x+4-10=0\\\Leftrightarrow (x+2)^2=\left(\pm\sqrt{10}\right)^2\\\Leftrightarrow \left[ \begin{array}{l}x=\sqrt{10}-2\\x=-\sqrt{10}-2\end{array} \right.\)

    Vậy nghiệm của phương trình là `S={-2+\sqrt{10}; -2-\sqrt{10}}`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )